Intelligent vehicle fault diagnosis system using Neural Networks - Paulraj, Murugesapandian; Sazali, Yaacob; Nor Shaifudin, Abd Hamid; Hema, Chengalvarayan Radhakrishnamurthy (Universiti Teknologi Mara, 2009)
Organized by Faculty of Electrical Engineering (UiTM), 9th - 11th March 2007 at Melaka.